Japanese Reforms After World War II - Syahbuddin Syahbuddin (STKIP Taman Siswa Bima, 2023)
This study aims to explain the background, direction and policy objectives of the Sukutu occupation government (SCAP) (Supreme Commander of the Allied Powers) under General Douglas MacArthur in Japan after World War II. This research is a library research with qualitative methods. Library research (library research), is research that utilizes library sources to obtain research data. The United States' occupation of Japan since 1945 was against the background of Japan's involvement in World War II which was driven by the spirit of imperialism to realize